Epstein-Barr Virus induces expression of the LPAM-1 integrin in B cells in vitro and in vivo - Delecluse, Susanne; Lasitschka, Felix; Bulut, Cem; Zeier, Martin (Journal of virology, 2019)
Epstein-Barr virus (EBV) infects the oropharynx but, surprisingly, frequently induces B cell proliferation in the gut of immunosuppressed individuals. We found that EBV infection in vitro induces the expression of the LPAM-1 integrin on tonsillar B cells and increases it on peripheral blood cells. Similarly, LPAM-1 was induced in the tonsils of patients undergoing primary infectious mononucleosis. EBV-induced LPAM-1 bound to the MAdCAM-1 addressin, which allows B cell homing to the gastrointestinal mucosa-associated lymphoid tissue (GALT). Thus, we hypothesized that EBV-induced LPAM-1 could induce relocation of infected B cells from the tonsil to the GALT. In situ hybridization with an EBER-specific probe revealed the frequent presence of EBV-infected cells in the pericolic lymph nodes of healthy individuals. Relocation of infected B cells into the GALT would expand the EBV reservoir, possibly protecting it from T cells primed in the oropharynx, and explain why EBV induces lymphoid tumors in the gut. - IMPORTANCE EBV causes tumors in multiple organs, particularly in the oro- and nasopharyngeal area but also in the digestive system. This virus enters the body in the oropharynx and establishes a chronic infection in this area. The observation that the virus causes tumors in the digestive system implies that the infected cells can move to this organ. We found that EBV infection induces the expression of integrin beta 7 (ITGB7), an integrin that associates with integrin alpha 4 to form the LPAM-1 dimer. LPAM-1 is key for homing of B cells to the gastrointestinal tract, suggesting that induction of this molecule is the mechanism through which EBV-infected cells enter this organ. In favor of this hypothesis, we could also detect EBV-infected cells in the lymph nodes adjacent to the colon and in the appendix.
Gesehen am 01.04.2019